Detection of venom by enzyme linked immunosorbent assay (ELISA) in patients bitten by snakes in Thailand. Issue 6569 (14th February 1987) - Silamut, K; Ho, M; Looareesuwan, S; Viravan, C; Wuthiekanun, V; Warrell, D A
Abstract : The ability of an enzyme linked immunosorbent assay (ELISA) to detect venom was evaluated in 251 patients bitten by four of the commonest poisonous snakes in Thailand. Serum was tested only from patients who brought the snakes that had bitten them. About one third of all bitten patients had detectable venom antigenaemia, though a smaller proportion were symptomatic. Serum venom concentrations on admission correlated with the severity of clinical manifestations. The test was sensitive and specific even for specimens that had been collected and stored under suboptimal conditions. The technique is suitable for forensic use in cases of suspected snakebite. The combination of snake identification and venom antigen detection should be a more reliable means of studying the epidemiology of snakebite than the measurement of venom antibodies in a population.